Integrating transcriptomics and metabolomics to reveal the protective effect and mechanism of Bushen Kangshuai Granules on the elderly people - Hu, Jun; Yang, Fengmin; Yang, Guang; Pan, Juhua; Tan, Yumeng; Tang, Yalin; Liu, Yongmei; Zhang, Hong; Wang, Jie (Frontiers in Pharmacology, 2024)
Background: Aging is characterized by a decline in the adaptability and resistance of the body. In this study, Bushen Kangshuai Granules (BKG), as a kind of Chinese herbal formula, was developed and shown to alleviate aging-related symptoms. Methods: Self-controlled study combined with RNA-seq and metabonomics were used to expound the efficacy and safety of BKG and revealed the regulation mechanism of BKG treating aging. In vitro experiments were used to confirm the analytical results. The aging cell model of AC16 cells were treated with D-galactose. The RT-qPCR was used to detect the impact of BKG on telomere length. The DCFH-DA staining was used for detecting intracellular ROS. The targeted signaling pathway was selected and verified using western blot. Results: After 8 weeks of treatment, BKG significantly reduced SOD level(P=0.046), TCM aging symptoms(P<0.001) and TNF-α level(P=0.044) in the elderly participants. High-throughput sequencing showed that BKG reversed the expression of 70 and 79 age-related genes and metabolites, respectively. Further enrichment analysis indicated that BKG down-regulated the PI3K-AKT signaling pathway, extracellular matrix (ECM)-receptor interaction, and Rap1 signaling pathway, while up-regulating sphingolipid metabolism. The results of in vitro experiments show that, after D-gal treatment, the viability and telomere length of AC16 cells significantly decreased(P<0.05), while the expression of ROS increased. (P<0.05), BKG significantly increased the telomere length of AC16 cells and reduced the level of ROS expression(P<0.05). In addition, BKG decreased the expression of THBS1, PDGFRA, and EPS8L1(P<0.05), consistent with the RNA-seq results. Our results also showed that BKG affects PI3K-AKT signaling pathway. Conclusion: BKG can significantly improve aging-related symptoms and increase SOD levels, which may be associated with the reversal of the expression of various aging-related genes. The PI3K-AKT signaling pathway and sphingolipid metabolism may be potential mechanisms underlying BKG anti-aging effects. Key words: Aging, Bushen Kangshuai Granules (BKG), Traditional Chinese medicine, transcriptomics, metabolomics